2013
DOI: 10.3390/ijms140713266
|View full text |Cite
|
Sign up to set email alerts
|

CD44 Is Associated with the Aggressive Phenotype of Nasopharyngeal Carcinoma through Redox Regulation

Abstract: Recent studies have shown that cancer stem-like cells (CSCs) within a tumor have the capacity for self-renewal and differentiation, and are associated with an aggressive phenotype and therapeutic resistance. Studies have also associated tumor progression with alterations in the levels of intracellular reactive oxygen species (ROS). In this study, we cultured nasopharyngeal carcinoma (NPC) CSCs in conditions that allowed sphere formation. The resulting sphere cells displayed stemness properties, characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…For example, increased expression of CD44 has been reported in tumorsphere cultures of MCF-7 cells [64]. Up regulation of CD44 in association with elevated levels of ROS was also reported in aggressive phenotype of nasopharyngeal carcinoma [65]. Increased expression of CD44 with down regulation of E-cadherin and increased number of soft agar colony formation in MCF-7 cells chronically exposed to H 2 O 2 in our study is consistent with previous reports.…”
Section: Discussionsupporting
confidence: 92%
“…For example, increased expression of CD44 has been reported in tumorsphere cultures of MCF-7 cells [64]. Up regulation of CD44 in association with elevated levels of ROS was also reported in aggressive phenotype of nasopharyngeal carcinoma [65]. Increased expression of CD44 with down regulation of E-cadherin and increased number of soft agar colony formation in MCF-7 cells chronically exposed to H 2 O 2 in our study is consistent with previous reports.…”
Section: Discussionsupporting
confidence: 92%
“…Because CD44 and CD133 are highly relevant to a CSC‐like phenotype in NPC cells, we, therefore, examined whether Snail could affect the expression of stem cell surface markers CD44 and CD133. The CNE2‐Snail cells showed a significant increase in the CD44‐positive, CD133‐positive, and CD44‐positive/CD133‐positive populations (93.7 ± 1.8%, 2.0 ± 0.2%, and 2.6 ± 0.3%, respectively) in comparison with their control counterparts (83.9 ± 2.5%, 0.8 ± 0.3%, and 1.0 ± 0.3%, respectively; P < .01, P < .01, and P < .01, respectively; Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have shown that the sorted CD44‐positive NPC cells showed a higher survival rate compared with CD44‐negative cells after radiation and chemotherapy . Studies have also shown that NPC contains a CD44‐positive subpopulation with features consistent with CSCs and there was a trend toward an association between CD44 expression within NPC tumors and decreased time to local failure/relapse in patients . The molecular structure of CD44 functions as a receptor for some ECM components, enabling CSCs to mediate signaling transduction to regulate CSC stemness properties.…”
Section: Discussionmentioning
confidence: 99%
“…EMT-type tumor cells are closely associated with tumor recurrence and therapeutic resistance and display several characteristics of CSCs [26]. Firstly, we investigated whether estrogen-treated breast cancer cells exhibited Gli1-dependent changes in cell motility using a wound healing assay in MCF-7 and HCC1428 cells.…”
Section: Resultsmentioning
confidence: 99%